2008
DOI: 10.1103/physreva.77.042705
|View full text |Cite
|
Sign up to set email alerts
|

Low-energy electron scattering from methanol and ethanol

Abstract: Measured and calculated differential cross sections for elastic ͑rotationally unresolved͒ electron scattering from two primary alcohols, methanol ͑CH 3 OH͒ and ethanol ͑C 2 H 5 OH͒, are reported. The measurements are obtained using the relative flow method with helium as the standard gas and a thin aperture as the collimating target gas source. The relative flow method is applied without the restriction imposed by the relative flow pressure conditions on helium and the unknown gas. The experimental data were t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
104
5
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 73 publications
(125 citation statements)
references
References 64 publications
15
104
5
1
Order By: Relevance
“…Figures 3(a)-3(d) depict the behavior of DCSs as a function of angle theta (q) for incident energies 5, 10, 15, and 20 eV, respectively. We have compared the present DCS results with the experimental and theoretical results of Khakoo et al [7] for the incident energies 5, 10, 15, and 20 eV while the theoretical results of Lee et al [4] are reported for incident energies 5 and 10 eV. Khakoo et al [7] have used the Schwinger multichannel pseudopotential method (SWCPP) and the Schwinger multichannel all electron method (SMCAE) to compute DCSs.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Figures 3(a)-3(d) depict the behavior of DCSs as a function of angle theta (q) for incident energies 5, 10, 15, and 20 eV, respectively. We have compared the present DCS results with the experimental and theoretical results of Khakoo et al [7] for the incident energies 5, 10, 15, and 20 eV while the theoretical results of Lee et al [4] are reported for incident energies 5 and 10 eV. Khakoo et al [7] have used the Schwinger multichannel pseudopotential method (SWCPP) and the Schwinger multichannel all electron method (SMCAE) to compute DCSs.…”
Section: Resultsmentioning
confidence: 99%
“…We have compared the present DCS results with the experimental and theoretical results of Khakoo et al [7] for the incident energies 5, 10, 15, and 20 eV while the theoretical results of Lee et al [4] are reported for incident energies 5 and 10 eV. Khakoo et al [7] have used the Schwinger multichannel pseudopotential method (SWCPP) and the Schwinger multichannel all electron method (SMCAE) to compute DCSs. For energies below 10 eV, the Static Exchange Polarization (SEP) model is considered and above it only the Static Exchange (SE) model is used by them [7].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations